How can we improve air pollution? Try increasing trust first - Fernando G. Cafferata; Bridget Hoffmann; Carlos G. Scartascini (Inter-American Development Bank (IDB), 2021)
Environmental policies are characterized by salient short-term costs and long-term benefits that are difficult to observe and to attribute to the government's efforts. These characteristics imply that citizens' support for environmental policies is highly dependent on their trust in the government's capability to implement solutions and commitment to investments in those policies. Using novel survey data from Mexico City, we show that trust in the government is positively correlated with citizens' willingness to support an additional tax approximately equal to a days minimum wage to improve air quality and greater preference for government retention of revenues from fees collected from polluting firms. We find similar correlations using the perceived quality of public goods as a measure of government competence. These results provide evidence that mistrust can be an obstacle to better environmental outcomes.
Keywords: Q53; Q52; Q56; H23; H41; H42; 330; Air pollution; Trust; Public services quality; Taxes; Public goods; Publicly provided private goods; Mexico